Vakalarla Kalp Damar Cerrahisi II - Uyar, Sami; Hanedan, Bedia Mine; Durmaz, Hüseyin; Çelik, Ersin; Erkan, Muhammet Hüseyin; Usta, Sefer; Demir, İbrahim; Beyaz, Metin Onur; Umaroğlu Öztürk, Sevi; Kurtoğlu, Murat; Acır, İbrahim; Atay, Mehmet; et al. (2023)
-